A mulher brasileira e portuguesa nas páginas da revista - Cavalcante, Andrea (2009)
The proposal of this dissertation is to examine how the discourses presented in editorials of woman magazines, such as Claudia and Maxima, Brazilian and Portuguese magazines respectively, build up the woman image in the 21th century. For this purpose it was used the methodology indicated by Discourse Analysis, in Maingueneau's reflexions. Due to the choosen theory, this work seeks to observe the enunciative scene and the interdiscourse, which was analysed from the heterogeneity presented in the selected discourses. It was possible to identify that the interdiscourse of samples and their respective enunciative scenes build up a different image between Brazilian and Portuguese women. Brazilian women bring together traditional and modern features and do not inquiry their social role, just seeking to address the issues that arise throughout life. Portuguese women reflect on their role, since their image is in the process of construction and the analyzed discourses cause these reflections. Key Words: interdiscourse, enunciative scene and woman